Omics : applications in biomedical, agricultural, and environmental sciences - Barh, Debmalya; Zambare, Vasudeo; Azevedo, Vasco (Boca Raton, Fla. : CRC Press/Taylor & Francis, 2013)
"With contributions from active researchers, this book explores emerging fields such as metagenomics, cytomics, glycomics, miRNA and their various applications, demonstrating the real diversity of omics. It covers cutting edge treatments such as toxicognenomics and its applications in assessment of environmental pollutants, applications of plant metabolomics, nutrigenomics and its therapeutic application, microalgal Omics and their applications in bio-fuel development. Next generation sequencing and Omics technology for transgenic plant analysis is also included"--Provided by publisher.
pt. I. The world of omics and applications in biomedical sciences -- pt. II. The world of omics and applications in plant and agricultural sciences -- pt. III. The world of omics and applications in environmental sciences.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Genomics; Agriculture; Biology -- Research; Ecology; Electronic books